1975
DOI: 10.1159/000279988
|View full text |Cite
|
Sign up to set email alerts
|

Über die transurethrale Schlitzung von Harnröhrenstrikturen unter endoskopischer Kontrolle

Abstract: From November 1972 to October 1974 190 patients of the ‘Urologische Klinik der Städt. Krankenanstalten Karlsruhe’ with urethral strictures were treated by internal urethrotomy under endoscopic control with the modified urethrotome from Stortz/Germany. This is a report about short-time results (2–14 months) after treatment. The method is very simple and the effect is controlled by endoscopy. In the first 44 patients we used general or lumbal anaesthesia. In the last patients only local anaesthesia by lnstillage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
0

Year Published

1977
1977
1989
1989

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…It is easy to perform and well tolerated even by frail pa tients. Sachse [ 1 ] reported a success rate of 80% and other authors report similar excellent results [2][3][4][5], In a pre vious study on the results of the operation, 67% of our patients were reasonably satisfied, although persistent strictures could be demonstrated in 50% of the cases [6]. Recently, similar results have been reported by other authors [7], The significance of the duration of the post operative treatment with indwelling catheter is uncertain.…”
supporting
confidence: 78%
“…It is easy to perform and well tolerated even by frail pa tients. Sachse [ 1 ] reported a success rate of 80% and other authors report similar excellent results [2][3][4][5], In a pre vious study on the results of the operation, 67% of our patients were reasonably satisfied, although persistent strictures could be demonstrated in 50% of the cases [6]. Recently, similar results have been reported by other authors [7], The significance of the duration of the post operative treatment with indwelling catheter is uncertain.…”
supporting
confidence: 78%
“…In 1971 Sachse designed a new instrument with a sharp blade which could cut the stricture under direct vision.He treated a large series of patients with t h s method and reported a success rate of 80 % (Sachse, 1974). Since then other series have been published reporting similar success (Elsasser et al, 1974;Matouschek and Michaelis, 1975).…”
mentioning
confidence: 78%
“…
Transurethral incision of urethral stricture is an old method of treatment. Maisonneuve (1854) and Otis (1872) invented urethrotomes which are still used today (Matouschek and Michaelis, 1975). These instruments are passed blindly and the stricture is cut without vision.
…”
mentioning
confidence: 99%
“…The introduction of the cold knife by Cervantes (Keitzer et af., 1961) and its adoption by Sachse for use in the urethra have simplified stricture treatment to such an extent that further significant changes are hard to imagine. Internal urethrotomy has indeed been advocated by many authors, with cure rates of up to 85% at the initial treatment being reported (Matouschek and Michaelis, 1975 ;Sachse, 1978;Gaches et al, 1979;Renders et al, 1979;Walther et al, 1980;Chilton et af., 1983;Smith et af., 1983;Stone et af., 1983).…”
mentioning
confidence: 99%